Induction of Th17 cell differentiation by B-1 cells - Wang, Yi; Rothstein, Thomas L. (Frontiers in Immunology, 2012)
B-1 cells constitute a unique B cell population with distinct ontogenic, phenotypic, and functional characteristics. Naïve, unmanipulated B-1 cells induce differentiation of CD4+ T cells to become pro-inflammatory Th17 cells whereas naïve B-2 cells do not. We examined the role of distinctly expressed surface membrane molecules in providing B-1 cells with Th17-differentiating function. Neither Mac-1, CD25, PD-L2 nor CD73 appeared to contribute to B-1 cell induction of Th17 differentiation. In contrast, we found that CD44 and CD86 are involved on the basis of studies with neutralizing antibodies and knock-out mice. Activation imparted to naïve B-2 cells the ability to induce Th17 differentiation and this was similarly partially interrupted by interfering with CD44 and CD86. Our findings suggest that CD44-OPN and B7 family members play important roles in the induction of Th17 cell differentiation by B cells.